Trauma Healing Kegiatan Bermain pada Anak-anak Pasca Erupsi Gunung Ruang Kabupaten Sitaro - Aror, Susanti Ch.; Lensun, Sherly F (CV. Kurnia Grup, 2024)
Mount Ruang, located in Sitaro district, North Sulawesi, erupted again on March 30, 2024. The impact of disasters is not only physical, so social-psychological aspects are now beginning to receive attention in overall disaster management. Volcanic eruptions produce harmful effects on the environment, climate, and health of exposed people, and are associated with a decline in social and economic conditions. The objectives of this service activity are to provide assistance to the community in the form of play activities as a trauma healing method for children after the eruption of Mount Ruang in Sitaro Regency, and how this approach can be effectively implemented in the context of local communities. Through this activity, children can express their feelings, rebuild their confidence, and reduce the anxiety they experience. In addition, support from parents and the community is needed to create a safe and supportive environment for children's recovery. By understanding the psychological impact of disasters and involving all parties in the recovery process, we can help children to not only recover from trauma, but also grow into stronger and more resilient individuals. Therefore, it is important to continue developing trauma healing programs that involve play activities and active participation from parents and communities.